Pengabdian Kepada Masyarakat melalui Program Bimbingan Belajar Bagi Anak Sekolah Dasar di Desa Patti - Andy S.K. Dahoklory; Lestari Lestari; Jekson N. Konoralma; Helen Rumurlely; Zusana Mose; Norce A. Anidlah; Yosafat A. Romer; Hermolina Fidratan; Rogerio Knyartutu; Viola V. Koryaru; Verlin J. Keilayoka; Vinolia Tunay (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
This community service aims to provide learning guidance for elementary school children. The implementation of this service was carried out by PSDKU Regency Real Work Lecture (KKN) students. Southwest Maluku in Patti Village. The method for implementing community service activities consists of three stages, namely planning, implementation and evaluation. Community service activities in the form of tutoring will be carried out from August – September 2023 3 times a week, at 16.00–17.30 WIT in the Patti Christian Elementary School study room. The tutoring participants are Patti Christian Elementary School children. Students provide study guidance material using lecture methods, practice questions and questions and answers. The tutoring activities that have been implemented are going well. The results of this activity have had a positive impact on the participants and are an example of how community service can help improve the quality of education at the basic level. Participants' ability to understand and solve practice questions well and correctly. Furthermore, basic English language skills and computer training have also increased among the children of Patti village.